Perspectives and attitudes of young patients with inflammatory bowel disease: symptoms, burden of disease and communication with their healthcare professionals. Issue 3 (13th December 2013) - Alexakis, C; Davies, G; Stephens, J; Clark, S; Rogers, S; Poullis, A
Abstract : Introduction: Inflammatory bowel disease (IBD) affects a significant proportion of young patients in the UK. The role of the healthcare professional, and their relationship with the young patient is particularly important at this difficult stage of their life, when education, social integration and career planning, can be dramatically affected by this consuming condition. Objectives: To address the attitudes, experiences and erspectives of young patients suffering from IBD, focusing particularly on the relationship between sufferer and healthcare provider. Methods: Crohn's and Colitis UK invited its young members to respond to a detailed internet based questionnaire addressing various aspects of patients' disease and their relationship with respective healthcare workers. Results: 1081 patients aged 29 years or less responded. Self reported burden of illness was high with only 12% respondents free from a disease flare in the previous 12 months with almost half being hospitalised in the same period. Quality of ommunication with healthcare providers was generally high, with three-quarters of patients feeling appropriately empowered in their healthcare decisions. The IBD nurse specialist was highlighted as a particularly valuable member of the team, scoring the highest of the professional groups in communication comfort scores, as well as being nominated by the patients as the preferred professional group to discuss their disease with. Conclusions: The results emphasize the considerable impact of the disease that this group is encumbered with, and identifies areas in the patient-professional relationship that can be augmented to improve the overall healthcare of this complex and fragile subgroup of patients.